The EFFECT OF DURATION AND AMOUNT OF SMOKING ON THE GROWTH OF STAPHYLOCOCCUS AUREUS: PENGARUH LAMA DAN JUMLAH MEROKOK PADA PERTUMBUHAN STAPHYLOCOCCUS AUREUS - EKA PUSPITASARI; Imelda Putri Kusharyati; Qurrotu A’yunin Lathifah (LPPM Universitas Abdurrab, 2025)
Smoking is a problem that is difficult to stop, causing dangerous impacts for smokers. Various diseases caused by smoking can cause death for active smokers and passive smokers in mild to severe degrees, such as the emergence of systemic or local pathological conditions in the mouth or throat. This occurs due to a decrease function and damage to the antioxidant components of saliva, which is followed by a decrease in function. Staphylococcus aureus is an oral bacteria that is commensal but can be a pathogen in humans causing nosocomial Objective: Is there a relationship between the duration of smoking and the amount of cigarette consumption on the growth of Staphylococcus aureus bacteria in active smokers. Methods: analytical observational with a cross sectional design. The sampling technique used was non-probability sampling with a purposive sampling method Results: were positive for Staphylococcus aureus as many as 20 respondents. Data analysis carried out using the Chi-Square test obtained a p value < 0.01 and data analysis on the amount of smoking obtained a p value < 0.003. Conclusions: There is a significant relationship between the duration and amount of cigarette consumption on the growth of Staphylococcus aureus bacteria in active smokers.